2020
DOI: 10.1111/sode.12486
|View full text |Cite
|
Sign up to set email alerts
|

Shy and still struggling: Examining the relations between subtypes of social withdrawal and well‐being in the 30s

Abstract: There is growing evidence that motivations reflecting social withdrawal are linked to various correlates and outcomes in childhood, adolescence, and emerging adulthood. However, little work has examined the subtypes of withdrawn motivations in early adulthood. Hence, the purpose of this study was to compare shy, avoidant, unsocial, mixed‐withdrawn, and non‐withdrawn men and women in early adulthood on indices of well‐being. This study drew on a large, representative U.S. sample of 5,000 participants (2,930 fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…Research on avoidance is in its infancy. Of the few studies examining the psychosocial outcomes of avoidance to date, all concluded that avoidance is costly throughout development (Closson et al, 2019; Coplan et al, 2018; Nelson, 2013; Nelson et al, 2021). It should be noted that females in this study were more test anxious than males.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research on avoidance is in its infancy. Of the few studies examining the psychosocial outcomes of avoidance to date, all concluded that avoidance is costly throughout development (Closson et al, 2019; Coplan et al, 2018; Nelson, 2013; Nelson et al, 2021). It should be noted that females in this study were more test anxious than males.…”
Section: Discussionmentioning
confidence: 99%
“…Coupled with low academic motivation, shyness may place emerging adults at risk for dropping out of university. Indeed, recent evidence indicates that shy adults are less educated and experience more regret surrounding their education and career than their unsociable and non-withdrawn counterparts (Nelson et al, 2021). Accordingly, strategies devised towards enhancing academic motivation through mentorship may have implications for university students high in shyness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Postponing romantic involvement to older ages than their more sociable counterparts might even be adaptive for withdrawn individuals. Having more time before focusing on “settling down” with a romantic partner could provide the opportunity to develop in other domains in which withdrawn young adults are also delayed, such as identity development (Barry et al, 2013 ), selecting educational and career paths (Hamer & Bruch, 1997 ), reaching higher levels of education and income (Nelson et al, 2020 ; Schmidt et al, 2017 ), maximizing person-environment fit (Shulman & Connolly, 2013 ), and developing interpersonal skills in other social relationships (e.g. friends, classmates, colleagues).…”
Section: Discussionmentioning
confidence: 99%
“…Left-behind adolescents are unable to experience positive interpersonal interactions from their parent-child relationships, because their parents provide less companionship and have di culty providing the security and social resources they need to develop freely. Therefore, left-behind adolescents have incompletely developed social ability and social adaptation (Barzeva et al, 2019;Bowker et al, 2014;Nelson et al, 2020), and it's hard for them to initiate friendships with peers. However, this study found that social support negatively predicted social withdrawal, similar to past research (Nonaka & Sakai, 2021).…”
Section: Effect Of Social Support On Social Withdrawalmentioning
confidence: 99%